Damping Ratio Estimation for a Slender Modular Building from Full Scale Ambient Response Monitoring - Fitzgerald, Breiffni; Broderick, Brian; Hickey, John; Moore, Hollie (My University, 2023)
The application of modular construction in tall slender structures is a relatively novel concept. Modular buildings with heights exceeding 130m have been successfully constructed by combining reinforced concrete cores with steel-framed volumetric modules. Slender structures typically have an increased susceptibility to wind-induced acceleration responses which may give rise to occupant discomfort, and modular structures are no exception. The lightweight nature of modular buildings implies that they are more likely to exhibit large horizontal accelerations than other more traditional forms of construction. As modular construction techniques are employed in ever taller, more slender buildings, design analysis requires better understanding and information about the dynamic behaviour of modular structures. The damping ratio of a structure is one of the key parameters in predicting its acceleration response. Typically, empirical damping ratio values obtained from previous full-scale testing are used when analysing the acceleration response of a structure and its compliance with habitability requirements. However, no suitable previous full scale monitoring campaigns have been carried out on tall modular buildings. This paper presents data obtained from a full-scale vibration monitoring campaign on the world’s tallest modular building. The ambient acceleration response of the 135 m tall modular structure was recorded over a three-month period. These data are processed using modal analysis techniques to estimate the fundamental natural frequency and damping ratio of the structure. The results obtained using Bayesian and random decrement-based techniques are compared and their dependence on the stage of construction is evaluated. The measurements were obtained when the building was in both partially- and fully constructed conditions, allowing the relative stiffness and damping contributions of the core and modules to be investigated. The results of this research provide greater insight into the dynamic behaviour of modular buildings increasing confidence in design analysis results and enabling modular construction to be pushed to new heights.
Experimental Vibration Analysis for Civil Engineering Structures
PUBLISHED
Milan
Keywords: Modal Identification; Wind-Induced Acceleration Response; Tall Buildings; Tall Volumetric Modular Construction; Damping Ratio; Ambient Vibration Monitoring; Smart & Sustainable Planet; Structural Dynamics; Structural Engineering